1999
DOI: 10.1007/bf03164932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tc-99m MDP, Tc-99m HSA and Tc-99m HIG uptake in rheumatoid arthritis and its variants

Abstract: Tc-99m polyclonal immunoglobulin-G has been shown to be a successful agent in the depiction of active inflammation in rheumatoid arthritis (RA). The objective of this study was to compare the uptake behaviors of Tc-99m HIG and Tc-99m MDP in RA and variants of rheumatoid arthritis (VRA). Seventeen patients with RA and 8 patients with VRA presenting with active inflammation were included in this study. Ten subjects with well-diagnosed degenerative joint disease constituted the control group. All joints in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Many of the studies have shown that nonspecific polyclonal human IgG scintigraphy is a useful test for localizing and detecting inflammatory joint activity and inflammation (23,24,25,26,27,28,29,30). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies have shown that nonspecific polyclonal human IgG scintigraphy is a useful test for localizing and detecting inflammatory joint activity and inflammation (23,24,25,26,27,28,29,30). …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, LPBS has been compared to HIG scintigraphy in inflammatory arthritis for only in the determination of the presence of inflammatory arthritis (24,29). However, there is not enough information about the agreement between LPBS - HIG scintigraphy in the determination of the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased uptake of 18  F-FDG in the joints is not specific for RA, as this also occurs in infectious and degenerative forms of osteoarthritis [32]. Radiolabeled diphosphonates do not locate primarily to inflammatory sites, but detect alterations in bone metabolism, especially increased pathological osteoblast activity [33,34]. SPECT imaging with 99m technetium-methylene diphosphonate ( 99m Tc-MDP) is clinically approved for the assessment of bone damage in RA and is used to monitor patients with active arthritis [33] (Figure 3).…”
Section: Emerging Techniques and Markers To Facilitate Molecular Imagmentioning
confidence: 99%
“…Radiolabeled diphosphonates do not locate primarily to inflammatory sites, but detect alterations in bone metabolism, especially increased pathological osteoblast activity [33,34]. SPECT imaging with 99m technetium-methylene diphosphonate ( 99m Tc-MDP) is clinically approved for the assessment of bone damage in RA and is used to monitor patients with active arthritis [33] (Figure 3). This tracer has proven to be useful for arthritis imaging in the past but provides limited insight into the disease process.…”
Section: Emerging Techniques and Markers To Facilitate Molecular Imagmentioning
confidence: 99%
“…Ergebnisse werden hier nicht berücksichtigt, es wird auf die Literatur verwiesen [7,8]. Ergebnisse werden hier nicht berücksichtigt, es wird auf die Literatur verwiesen [7,8].…”
Section: Spezifische Gelenkszintigraphieunclassified